Thalassemia carrier screening in siblings of thalassemia major patients by HbA2 estimation - Sharma, Gopikishan; Sharma, Dipendra; Gulati, R K (Indian Journal of Child Health, 2016)
Objective: Thalassemia carrier screening in siblings of thalassemia major patients by HbA2 estimation. Methods: This prospective, cross-sectional study was conducted at thalassemia welfare society of JK Lon Hospital, Kota. Siblings of thalassemia major patients registered at our hospital were investigated for chemically bonded ceramics and HbA2 estimation by high performance liquid chromatography (HPLC) method. Results: A total of 121 cases were screened for carrier by HPLC method for HbA2 estimation. Total 59 (48.76%) cases had HbA2 level ?3.5%, and considered as carrier while 62 (51.24%) cases were non-carrier. Mean HbA2 value in carrier was 5.24% ± 1.14% and in non-carrier was 2.69% ± 0.51%. Conclusion: It was concluded that ? thalassemia carriers are more prevalent in siblings of thalassemia major than the normal population.